Long-term monitoring across elevational gradients (III) : vascular plants on Terceira Island (Azores) transect - Henriques, Débora (2017)
Anthropogenic disturbance often drives habitat loss, ecological fragmentation and a decrease in biodiversity. This is especially problematic in islands, which are bounded and isolated systems. In the Azores, human settlement led to a significant contraction of the archipelago’s original native forested areas, which nowadays occupy only small patches and are additionally threatened by the spread of invasive species. Focusing on Terceira Island, this study aimed to assess the composition of vascular plant communities, and the abundance and distribution patterns of vascular plant species in permanent 100 m2 plots set up in the best preserved vegetation patches along an elevational gradient (from 40 to 1000 m a.s.l.). Sampling yielded a total of 50 species, of which 41 are indigenous and nine are exotic. The richest and best preserved communities were found between 600 m and 1000 m, corresponding to Juniperus-Ilex montane forest and Calluna-Juniperus altimontane scrubland formations. Nonetheless, exotic species were prevalent between 200 m and 400 m, with Pittosporum undulatum clearly dominating the canopy. These results support the high ecological and conservation value of the vegetation formations found in the island’s upper half, while calling attention to the biological invasions and homogenization processes occurring at its lower half. Long-term monitoring in these plots will further reveal direction and rates of change in community composition, allowing for more informed management and conservation strategies in the island.